The Strategic Mind the journey to leadership through strategic thinking - Gorzynski. Bob (Gloucestershire Management Books 2000 Ltd, 2009)
The world as we know it is changing rapidly and beyond recognition. To move towards a 'world that works for all' will require a profound shift in the way that we think - and the capacity for each one of us to become a leader in initiating change in our own lives, businesses and communities to begin to live in long-term sustainable harmony with the world around us. "The Strategic Mind" provides a framework for developing a deeper, more holistic form of thinking using seven core disciplines: know your own story; think small; go slowly; serve others; reflect; be simple; and, dream. Packed with examples and case studies from the very large (BP, Amazon, Apple) to the very small, the book provides both theoretical insight and practical guidance for the 21st-century manager wanting to develop a sustainable business strategy, responsive to the needs of the wider community as well as to the needs of shareholders, employees, customers, suppliers, and business partners.
Includes Index (pg.249-252)
Keywords: Leadership